Exposure to naphthalene and β-pinene-derived secondary organic aerosol induced divergent changes in transcript levels of BEAS-2B cells. (August 2022) - Pardo, Michal; Offer, Svenja; Hartner, Elena; Di Bucchianico, Sebastiano; Bisig, Christoph; Bauer, Stefanie; Pantzke, Jana; Zimmermann, Elias J.; Cao, Xin; Binder, Stephanie; Kuhn, Evelyn; Huber, Anja; et al.
Graphical abstract: Highlights: A comprehensive comparison between SOANap -SP and SOAβPin -SP shows differences in their chemical composition. SOANap -SP has a higher cytotoxic potential than SOAβPin -SP. SOANap -SP has stronger potency in inducing inflammatory and genotoxicity response than that of SOAβPin -SP. SOANap -SP activates Nrf-, AhR-, MMP- and MAPK signaling pathways. Abstract: The health effects of exposure to secondary organic aerosols (SOAs) are still limited. Here, we investigated and compared the toxicities of soot particles (SP) coated with β-pinene SOA (SOAβPin -SP) and SP coated with naphthalene SOA (SOANap -SP) in a human bronchial epithelial cell line (BEAS-2B) residing at the air–liquid interface. SOAβPin -SP mostly contained oxygenated aliphatic compounds from β-pinene photooxidation, whereas SOANap -SP contained a significant fraction of oxygenated aromatic products under similar conditions. Following exposure, genome-wide transcriptome responses showed an Nrf2 oxidative stress response, particularly for SOANap -SP. Other signaling pathways, such as redox signaling, inflammatory signaling, and the involvement of matrix metalloproteinase, were identified to have a stronger impact following exposure to SOANap -SP. SOANap -SP also induced a stronger genotoxicity response than that of SOAβPin -SP. This study elucidated the mechanisms that govern SOA toxicity and showed that, compared to SOAs derived from a typical biogenic precursor, SOAs from a typical anthropogenic precursor have higher toxicological potency, which was accompanied with the activation of varied cellular mechanisms, such as aryl hydrocarbon receptor. This can be attributed to the difference in chemical composition; specifically, the aromatic compounds in the naphthalene-derived SOA had higher cytotoxic potential than that of the β-pinene-derived SOA.